EFEKTIVITAS WAKTU PENGGENANGAN AIR TERHADAP PENGAWETAN LENGAS TANAH PADA TANAMAN KEDELAI - Aminah, A; Abdullah, A; Nuraeni, N; Palad, Marlyana S. (Journal Galung Tropika, 2019)
Important factors that form the basis of water management are plant characteristics based on water requirements, the amount of water supplied, irrigation methods, and soil characteristics to conserve water. These factors are also influenced by local agroecological conditions such as climate, soil type, and availability of irrigation water. The study aimed to determine the effectiveness of inundation time on soybean growth and production to maintain soil moisture. The study was arranged in an experimental form using a Randomized Block Design (RBD) consisting of waterlogging time treatment (W), ie not flooded/field capacity (W0), inundation 0-15 days after planting (dap) (W1), inundation 15-30 dap (W2), inundation at 30-45 dap (W3), and inundation continuously until harvest (W4). The height of the water given was 5 cm. The results showed that continuous inundation until harvest increased the weight of seeds by 19.23% compared without inundation. This was evidenced by the increasing number of pods and number of seeds per plant by 31.1% and 37.59% compared to field capacity. Continuous inundation showed that the highest soil water content (moisture) compared to other treatments. As for the greenness of leaves, inundation at 15-30 dap showed the lowest greenness of leaves while the highest greenness of leaves is inundation 0-15 dap, and this was not significantly different from other treatments. Continuous inundation has shown the potential to increase soybean yield. These results indicated that the irrigation method until the soil was saturated with water or above the field capacity was still quite safe for the growth, development, and production of soybean plants.